Drivers of eco-innovation: the role of appropriability strategies and complementary assets - Orjuela-Ramirez, Guillermo; Zuluaga Jimenez, Julio Cesar; Urbano, David (Oxford University Press, 2024)
How do eco-innovators protect and profit from their innovations so they have the incentive to undertake an innovation in the first place? The double externality nature of environmental innovations intricates this appropriability problem, as competitors and society might also benefit from the value created by eco-innovation. Based on David Teece’s Profiting from innovation framework, we argue that firms combine appropriability strategies such as patents, industrial secrecy, and complex design with the development of complementary assets to incentivize and secure rent appropriation from eco-innovation. We estimate that formal appropriability mechanisms increase the probability of developing an eco-innovation by 6 per cent, while informal mechanisms increase it by about 15 per cent. Our panel data regression model demonstrates that marketing capability enhances the effect of appropriability mechanisms by differentiating eco-innovation from other technologies. However, this complementarity differs as a firm increases marketing investments, especially in small and Research and Development R&D publicly financed firms.